The Health Education on Basic Life Support Improves Knowledge and Skills of Red Cross Youth Members - Atiqoh, Ummu; Supriyanto, Supriyanto; Anugrahini, Hepta Nur; Hamid, Irfany Nurul (Universitas Tribhuwana Tunggadewi, 2025)
The Youth Red Cross (PMR) is a pioneer in the field of health in schools, which can play a role in assisting victims if they need Basic Life Support (BLS). The level of knowledge and skills of PMR members is significantly lacking regarding BLS actions, while victim handling and BLS actions require knowledge and skills. The purpose of this study was to determine the effect of BLS Health Education on the Level of Knowledge and Skills of PMR Members at MAN 2 Kota Madiun. This research method is one group Pretest-Posttest with Wilcoxon sign rank analysis test. The intervention of this study was health education using PowerPoint media, booklets, and audiovisual. Before the intervention 19% had a good level of knowledge and after the intervention, 81% had a good level of knowledge with p=0.00. The skill level before the intervention was 0%, with no participants having a good skill level, 65% had a good skill level with p=0.00. The results of statistical tests show that there is an effect of BLS Health Education on the level of knowledge and skills of PMR members. Health Education with Audiovisual, PowerPoint, and Booklet can increase knowledge and skills in BLS Action because this method is an effective learning method that is easy for someone who receives the material. This media can be used for further research.